The 2008 Battle of Sadr City Reimagining Urban Combat - Johnson, David E. (RAND Corporation, 2013)
In 2008, U.S. and Iraqi forces defeated an uprising in Sadr City, a district of Baghdad with ~2.4 million residents. Coalition forces' success in this battle helped consolidate the Government of Iraq's authority, contributing significantly to the attainment of contemporary U.S. operational objectives in Iraq. U.S. forces' conduct of the battle illustrates a new paradigm for urban combat and indicates capabilities the Army will need in the future.